2019
DOI: 10.1159/000496978
|View full text |Cite
|
Sign up to set email alerts
|

Ramucirumab and Paclitaxel Administered Every 2 Weeks (mRAINBOW Regimen) in Advanced Gastroesophageal Adenocarcinoma

Abstract: Background: The RAINBOW trial established ramucirumab combined with paclitaxel as a second-line option in metastatic gastric and gastroesophageal junction (GEJ) adenocarcinoma. Ramucirumab was given on days 1 and 15 with paclitaxel on days 1, 8, and 15 of a 28-day cycle. The median overall survival (OS) was significantly longer with ramuciru­mab plus paclitaxel (p = 0.017), and it led to 41% grade 3 or higher neutropenia. We review our experience with both ramucirumab plus paclitaxel given biweekly (mRAINBOW) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…12,13 The alternative schedule of ramucirumab 8 mg/kg plus paclitaxel 110 mg/m 2 given once every 2 weeks has also been evaluated in a retrospective single-center database analysis. 14 The authors of that analysis considered that this amended dosage regimen did not compromise efficacy in the second-line setting (overall survival 9.46 months 14 vs 9.6 months in RAINBOW 5 ), although dose delays, adjustments, and omissions were similar to those reported in the RAINBOW trial. Overall, 31% of patients receiving the alternative treatment regimen as second-line therapy, and 32.5% receiving this regimen as second-line or greater therapy, required a dose or schedule modification, most commonly because of neutropenia (44% of delays or adjustments in the total population), and occasionally neuropathy (3.6%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…12,13 The alternative schedule of ramucirumab 8 mg/kg plus paclitaxel 110 mg/m 2 given once every 2 weeks has also been evaluated in a retrospective single-center database analysis. 14 The authors of that analysis considered that this amended dosage regimen did not compromise efficacy in the second-line setting (overall survival 9.46 months 14 vs 9.6 months in RAINBOW 5 ), although dose delays, adjustments, and omissions were similar to those reported in the RAINBOW trial. Overall, 31% of patients receiving the alternative treatment regimen as second-line therapy, and 32.5% receiving this regimen as second-line or greater therapy, required a dose or schedule modification, most commonly because of neutropenia (44% of delays or adjustments in the total population), and occasionally neuropathy (3.6%).…”
Section: Discussionmentioning
confidence: 97%
“…Overall, 31% of patients receiving the alternative treatment regimen as second-line therapy, and 32.5% receiving this regimen as second-line or greater therapy, required a dose or schedule modification, most commonly because of neutropenia (44% of delays or adjustments in the total population), and occasionally neuropathy (3.6%). 14 In RAINBOW, 24% of patients randomized to ramucirumab plus paclitaxel had a paclitaxel dose reduction, and among this treatment group, 38%, 8%, 0%, and 0% experienced grades 1–2, 3 and 4, neuropathy, respectively, and 14%, 71%, and 62% experienced these grades of neutropenia, respectively. 5 …”
Section: Discussionmentioning
confidence: 99%
“…We propose skipping the administration of paclitaxel /nab-paclitaxel at day 8 to avoid neutropenia and to reduce the frequency of hospital visits. A previously published study has indicated that biweekly administration of ramucirumab plus paclitaxel did not compromise efficacy [45].…”
Section: Palliative Chemotherapymentioning
confidence: 94%
“…We selected the modified RAINBOW (mRAIN-BOW) bi-weekly simplified regimen (paclitaxel 110 mg/m 2 plus ramucirumab 8 mg/kg every 2 weeks) as our standard according to the MD Anderson study. 23 Whenever ramucirumab was contraindicated or not available, second-line chemotherapy consisted of 3weekly courses of docetaxel or irinotecan (provided pharmacogenomic testing results were available).…”
Section: Gastric and Gastroesophageal Cancermentioning
confidence: 99%